Factors Determining Wage Differentials in the Americas - Jecchinis, Chris; Harris, T. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1974)
This paper reviews factors that determine wage differentials in the developing and the developed countries of the Americas and considers consequent policy questions.